The impact of chemotherapy on floating vs. attached colorectal cancer cells: An in-vitro study - Khosrawipour, Veria; Mikołajczyk-Martinez, Agata; Khosrawipour, Carolina; Salata, Patrycja; Kiełbowicz, Zdzisław; Nicpon, Ewa; Przadka, Przemyslaw; Zhang, Zhiwen; Kielan, Wojciech; Li, Shiri; Bania, Jacek; Kuzniak, Kamila; et al. (Frontiers in Oncology, 2026)
BackgroundPeritoneal metastasis (PM) is a highly aggressive, hard-to-treat malignant disease which has continuously increased in incidence and clinical urgency. The progression of peritoneal metastasis (PM) is primarily driven by the spread of intraperitoneal cancer cells through initial surface adhesion, followed by growth and local invasion. Therefore, prevention of this initial adhesion may help to inhibit metastatic formation. By using a novel in-vitro PM model, this study investigates the inhibitory effect of chemotherapy on floating colorectal cancer cells compared to attached cells. The study intends to evaluate whether floating cancer cells are more sensitive to chemotherapy than attached ones.MethodsHT-29 colorectal cancer cells were exposed to oxaliplatin (OX) and doxorubicin in-vitro while in an attached vs. floating state. Cell viability was assessed using MTS assay, and intracellular chemotherapy uptake was measured via flow cytometry. Both groups were compared regarding metastatic colony formation using a novel in-vitro peritoneal metastasis model created by laparoscopically harvesting peritoneal progenitor cells.ResultsOX exposure to floating cancer cells significantly reduced cell adhesion and viability compared to OX exposure to attached cells (p < 0.05). Flow cytometry revealed that this effect was not due to increased chemotherapy uptake in floating cells. In the in-vitro peritoneal cancer cell model, floating cancer cells treated with OX showed a markedly reduced ability to form cancer metastasis.ConclusionsChemotherapy administered to cancer cells prior to full surface adhesion strongly impairs cancer cell adhesion, growth, and expansion. This phenomenon may partly explain the favorable clinical outcomes observed with (neo)adjuvant chemotherapy before and after complete cancer resection in PM and other cancer types. Floating cells seem to be more sensitive to chemotherapeutic agents than attached cells. Delaying and targeting specifically the ability of cancer cells to attach could help enormously in the treatment of many cancer manifestations such as PM. Further research is needed to confirm these findings in other cancer entities and to explore their potential clinical applications.